Pendidikan karakter : menjawab tantangan krisis multidimensional - Muslich, Masnur, 1956- (Jakarta : Bumi Aksara, 2011)
On character education in Indonesian schools.
Includes bibliographical references (p. 215-222).
Teks dalam Bahasa Indonesia.
Keywords: Moral education -- Indonesia; Character